Implementasi Edukasi Digital Marketing untuk Meningkatkan Penjualan UMKM Dusun Karya Harapan Mukti Kecamatan Pelepat Ilir Kabupaten Bungo Provinsi Jambi - Nia Putri Agustina; Muhammad Dafit; Nur Fadilah; Moch Anwar Zaenudin; Bardan Mudaini; Prengki Ade Candra; Ujang Ruhyat Syamsoni (khidmatan, 2026)
This community service activity was motivated by the limited use of digital marketing in the Keripik Singkong Barokah micro and small enterprise in Dusun Karya Harapan Mukti, Pelepat Ilir District, Bungo Regency, Jambi Province, where product promotion had mainly relied on word-of-mouth communication and WhatsApp messages, resulting in a narrow market reach. The activity aimed to improve the partner’s knowledge and skills in using digital media for product promotion while strengthening the business identity of the enterprise. The target partner was the Keripik Singkong Barokah business group, involving seven participants, including the business owner. The implementation employed the Participatory Action Research approach through stages of problem identification, observation, interviews, participatory discussion, digital marketing education, promotional design training using Canva, assistance in creating an Instagram account, and strengthening business accessibility through banner installation. The results showed an increase in the partner’s understanding of the importance of digital marketing, improved skills in designing promotional content, the availability of a business social media account, and stronger business visibility in both online and offline settings. The activity also encouraged a positive change in attitude, as the partner became more confident, more open to technology, and better prepared to manage promotion independently. Overall, this program is relevant as a practical, contextual, and sustainable model of rural business empowerment for home-based food enterprises.